Field notes contributed by Francis L. Moore, fall 1982 - Moore, Francis L.et al (1982)
Field notes were contributed by Francis L. Moore and other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1982. Epson - sheet feed